Assess the possibility of using DNA barcodes in the identification of bird specimems in Vietnam National Museum of Nature - Thanh, Tran Thi Viet; Duy, Vu Dinh; Tam, Nguyen Minh (Academia Journal of Biology, 2015)
Based on determining DNA barcode sequences (CO1 gene sequences of the mitochondrial genome), Four bird samples of family (Timaliidae), viz. 005_BTTNVN, White collared Yuhinas; 028_BTTNVN, Rufous winged fulvetta; 045_BTTNVN, White-browed fulvetta and 055_BTTNVN, Black-faced Laughingthrush were identified. Total DNA was extracted from samples of blood, then proceed with polymerase chain reaction (PCR), purification and sequencing using pairs of primers Barcode program CO1 DNA Barcoding BirdF1-BirdR1. The results have identified DNA sequence fragment about 650bp. Analysis by computer software Mega 5.2.2 and the program BLAST on the international genbank shows the specimens with the genus have exactly the name as identification by morphology. The DNA sequences were registered in GenBank with code: KP768404, KP768405, KP708406, KP768407. With the results obtained, we belive that successfully use of primers BirdF1-BirdR1 for identification of assessment for birds to serve multiple samples exhibited at the Vietnam National Museum of Nature, while contributing to the protection of genetic resources of Vietnam quarter, integration with the world Barcoding Project.